Quality of sleep, health and well-being in a population-based study - Marilisa Berti de Azevedo Barros; Margareth Guimarães Lima; Maria Filomena Ceolim; Edilson Zancanella; Tânia Aparecida Marchiori de Oliveira Cardoso
ABSTRACT OBJECTIVE To estimate the prevalence of poor self-rated sleep and to identify the population subgroups most susceptible to the problem. METHODS This is a cross-sectional, population-based study developed with data from the Health Survey conducted in the city of Campinas (ISACamp 2014/2015). Data from a sample of 1,998 individuals aged 20 years or older were analyzed. The self-rated quality of sleep was analyzed according to socio-demographic characteristics, morbidities, health behaviors and feeling of well-being. The association of sleep quality with different complaints and characteristics of sleep was also analyzed. Adjusted prevalence ratios were estimed using Poisson multiple regression model allowing for the sample weights. RESULTS Prevalence of poor self-rated sleep was 29.1% and showed to be significantly higher in women, in individuals aged from 40 to 50 years, migrants, without occupation, physically inactive in leisure context, with common mental disorder (PR = 1.59), with greater number of health problems (PR = 2.33), poor self-rated health (PR = 1.61), and life dissatisfaction. Poor sleep was strongly associated with reports of difficulty in initiating sleep (PR = 4.17), in maintaining sleep (PR = 4.40) and with never or almost never feeling well when waking up (PR = 4.52). CONCLUSIONS The results identify the population subgroups with poor quality of sleep that deserve greater attention. It also highlight the need to consider, in addition to the presence of comorbidities, mental health and the feeling of well-being in the care of patients with sleep problems and in the interventions planed for promoting healthy sleep.